A constructivist approach to the design and delivery of an online professional development course: a case of the iEarn online course - Chitanana, Lockias (International Journal of Instruction, 2016)
This study examined the International Education and Resource Network Science Technology and Math (iEARN-STM) online professional development course. The study used the constructivist framework as the conceptual model to examine the way in which the constructivist theory has shaped the design and implementation of the course, as reflected by the interactions of a cohort of participants in the course. The participants were 28 educators enrolled in the course, who were either teacher educators or teachers, working in different educational institutions in different countries throughout the world. The purpose of the study was to understand how the iEARN online professional development course supported teachers’ learning through effective discourse in an online environment and to identify the constructivist learning principles that were behind the success of the course. The design of the course appeared to have a positive impact on participants’ collaboration with peers. Results of the study confirms earlier research findings that the constructivist approach to course design and delivery provides a powerful structure for creating learning environments conducive to the development of professional skills among educators. Results of this study can be used to assist professional development coordinators and administrators to plan effective professional development. The results of the study are also expected to contribute to improvements in the design of professional development course content, instruction, delivery and administration, focusing on factors such as program model, delivery, contextual factors or best practices.